Biology Teaching Methodology and its Modern Methods - G‘afforovna, Bo‘riyeva Guljahon (European Journal of Life Safety and Stability (2660-9630), 2022)
In this Article we discuss the different effective methods of teaching biology. Biology is one of the central branches of scientific knowledge and is relevant to topics including medicine, genetics, zoology, ecology, and public policy. As such, it has the potential to interest almost any student. To be successful at teaching biology, however, you will have to think carefully about how to share this exciting field in ways that are relatable and enjoyable. Along the way, you should make it your goal for students to achieve at least a fundamental knowledge of biological concepts.